PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN MENULIS TEKS EKSPOSISI PADA SISWA KELAS X IIS-4 SMA NEGERI 8 MAKASSAR - Kurnia Kurnia (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2015)
This Study was a classroom action research which aimed at describe the plan, implementation, and the enhancement of exposition text writing ability of class X IIS-4 SMAN 8 Makassar by employing Problem-based learning model. The samples were 36 studentsstudents of class X IIS-4 students at SMAN 8 Makassar academic year 2014-2015. The study was conducted in two cycles, namely cycle I and cycle II. Each cycle consisted of two meetings. At the implementation stage of the cycle I and cycle II, observation sheet and test of exposition text writing ability Wet employed to collect the data needed and as the of students' benchmark of exposition text writing ability based on the minimal mastery criteria, 75. The results of the study revealed that the students’ writing text of class X IIS-4 at SMAN 8 was enhanced by employing Problem-based learning model in the planning, action, observation, evaluation stages. The subject teacher was considered as successful to enhance and conduct the lesson plan which showed good score. At the action stage, the students had good behavior. At the evaluation stage, the test result of exposition text writing ability in terms of content, text structure, vocabulary, sentences, and mechanics indicated that in cycle I students had not achieved the set mastery level. At the cycle II, students had achieved the learning master of exposition text writing. The conclusion based on the study was the Problem-based learning model could enhance exposition text writing ability of class X IIS-4 SMAN 8 Makassar after conducting in two cycles.